Implementation of Balanced Scorecard and The Successful of Implementation Strategy: A Review - Lena Ellitan; Lina Anatan (Universitas Kristen Maranatha, 2008)
The balanced scorecard is a formal management technique for development, implementation and management of business strategy. It is difficult to ascertain the success of the technique as most of the literature on its implementation is put out by those with a vested interest in its success as a commercial product. Much has been written about barriers to strategy implementation but not specifically to the implementation of balanced scorecard. This paper presents a review of the factors that contributed to the successful implementation of strategy through implementation of balanced scorecard. While balanced scorecard methodology attempts to overcome some of the barriers to implementation of strategy, factors such as leadership, cultural readiness and organizational learning need to be addressed before any implementation of strategy.